Analysis of Actual Operation and Maintenance Cost Requirements (AKNOP) for the Cikahuripan Irrigation Network in Sukabumi Regency - Cece Suhendi; Ardin Rozandi (Marasofi International Media and Publishing (MIMP), 2026)
The Cikahuripan Irrigation Area in Sukabumi Regency plays an important role in supporting agricultural productivity, particularly rice cultivation. However, the irrigation network has experienced functional degradation due to sediment accumulation, erosion, and malfunctioning water control structures, resulting in suboptimal water distribution. This study aims to determine the Actual Operation and Maintenance Cost Requirement (AKNOP) and identify priority maintenance activities needed to restore irrigation performance. The research employed an observational method through field inspections, inventory surveys, and analysis of irrigation infrastructure conditions. Primary and secondary data were collected from relevant agencies and direct observations. The AKNOP calculation was carried out by identifying operation and maintenance activities, determining work volumes, and estimating costs based on applicable unit price analyses. The results showed that the total AKNOP for the Cikahuripan Irrigation Network was Rp. 493,240,000, consisting of operation costs of Rp. 132,302,800 (30%), routine maintenance costs of Rp. 293,306,813 (65%), and periodic maintenance costs of Rp. 22,731,003 (5%). The study concludes that routine maintenance activities constitute the largest expenditure due to the extensive deterioration of irrigation facilities. It is recommended that responsible agencies prioritize sediment removal, vegetation control, and repair of damaged structures. The findings provide a practical basis for budgeting and improving irrigation management to support sustainable agricultural productivity.